25 toughest sales objections (and how to overcome them) : surefire techniques for conquering any resistance and closing the deal - Schiffman, Stephan (New York : McGraw Hill, 2011)
The 25 Toughest Sales Challenges-and How to Overcome Them helps you reverse buyer resistance by illustrating how and why these frustrating objections come up, what they mean, and what to say and do to neutralize them. Stephan Schiffman offers specific questions that keep the sales dialogue going in the toughest situations. Filled with tips, techniques, and dialogue scripts, The 25 Toughest Sales Challenges-and How Overcome Them empowers you to become the buyer's trusted problem solver and bypass future objections before they even arise.
Includes index.
Keywords: Selling